2019
DOI: 10.1039/c9ra02843a
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic carbonate composites as potential high temperature CO2 sorbents with enhanced cycle stability

Abstract: A Ca/Mg/Al oxide composite was synthesised and showed a high CO2 uptake of 0.537 g g−1 at 650 °C with high uptake even after 100 cycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 36 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…Modied CaCO 3 and MgCO 3 also showed high stability with 1% loss in CO 2 uptake capacity aer 23 cycles. 19 Overall, NHO-1 and 1.25 can be considered to be chemically and structurally stable aer repeated carbonation and calcination when compared with other sorbents. We are aware that as our experiments were performed using pure CO 2 and N 2 , they cannot be considered to be realistic for real-life applications.…”
Section: Cycling Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Modied CaCO 3 and MgCO 3 also showed high stability with 1% loss in CO 2 uptake capacity aer 23 cycles. 19 Overall, NHO-1 and 1.25 can be considered to be chemically and structurally stable aer repeated carbonation and calcination when compared with other sorbents. We are aware that as our experiments were performed using pure CO 2 and N 2 , they cannot be considered to be realistic for real-life applications.…”
Section: Cycling Stabilitymentioning
confidence: 99%
“…Sintering reduces the accessible surface area available for the reaction between CO 2 and the sorbent, which decreases the CO 2 uptake capacity. 18 In order to improve the performance of inorganic oxide sorbents, researchers have focused their research on (1) preventing sintering by adding a thermal stabilizer to the sorbents [19][20][21][22][23] or (2) developing sorbents with high cycling stability. [24][25][26] Zirconium-based inorganic oxides such as Na 2 ZrO 3 , Li 2 ZrO 3 , and K 2 ZrO 3 have attracted attention in recent decades as potential CO 2 sorbents.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Vall et al 56 employed MgO and Al 2 O 3 to stabilise a synthetic CaO sorbent, obtained by calcining highly porous amorphous calcium carbonate (HPACC -BET surface area of over 450 m 2 /g). Whilst MgO alone can effectively stabilise the CaO sorbent, the sorbent synergistically stabilised by both MgO and Al 2 O 3 yielded even higher stability, showing only a 2.8 % decrease in the CO 2 uptake capacity after 23 cycles (1 st cycle 54.2 wt.% (69.1 mol%).…”
Section: 2mentioning
confidence: 99%
“…Figure 3. Scanning electron micrograph of CaO stabilised with both MgO and Al 2 O 3 a) as-synthesized and b)after 23 cycles of carbonation/calcination 56. …”
mentioning
confidence: 99%
“…[ 143 ] Sun et al [ 144 ] showed the positive effect of CeO 2 against sintering for the CaO‐based sorbent. Moreover, Vall et al [ 145 ] used MgO and Al 2 O 3 to stabilize a synthetic CaO sorbent using co‐precipitation method. It was shown that the sorbent synergistically stabilized by both MgO and Al 2 O 3 , resulting in high stability with only a 2.8% decrease in the CO 2 uptake capacity after 23 cycles.…”
Section: Synthetic Sorbentsmentioning
confidence: 99%